Flexible Work Practices (FWP) – An effective instrument in the retention of talent: A survey of selected JSE-listed companies - P. A. Grobler; A. J. De Bruyn (South African Journal of Business Management, 2011)
There is a paucity of research available on the use of flexible work practices (FWP) in South African companies. The primary aim of this study was to close this gap by determining to what extent listed companies on the JSE in the very important sectors of Finance, Telecommunications and Technology make use of these practices. A secondary aim was to establish whether companies perceived any advantages, disadvantages, barriers and solutions when implementing or thinking to implement these practices. Although neither disadvantages nor barriers were found, significant differences between the usage of these practices and some corpographic variables such as the size of staff, nature of competition and the business unit strategies followed, were found. It also became clear that although these practices were available within companies, the percentage of staff making use of them were very small. However, a number of advantages regarding the use of these practices were identified by companies, as well as a number of solutions to successfully implement these practices in companies. The study concludes that companies should seriously consider expanding the use of these practices as numerous benefits exist for the company, the employee and the larger community.
Keywords: 650